2017
DOI: 10.12783/dtmse/amsee2017/14277
|View full text |Cite
|
Sign up to set email alerts
|

Research on Physical and Mechanical Characteristics of Recycled Aggregate Concrete

Abstract: Development and utilization of recycled aggregate concrete can solve the processing difficulties caused by a lot of waste concrete. Experiments results showed the higher replacement percentage of recycled aggregate concrete, the lower its bulk density. Both drying shrinkage degree and drying shrinkage sustained time of recycled aggregate concrete increase with increasing its replacement percentage. The ultimate bearing capacity of recycled aggregate concrete decreases as its replacement percentage increases. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…If the circulation ratio / is equal to 1, the point (1, 1) will locate on the curve of formulas (4) and (5). Via the two formulas, values of can be deducted as formula (6), which correspond to the maximum fatigue stress and the residual fatigue stress.…”
Section: Fatigue Strain Evolution Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…If the circulation ratio / is equal to 1, the point (1, 1) will locate on the curve of formulas (4) and (5). Via the two formulas, values of can be deducted as formula (6), which correspond to the maximum fatigue stress and the residual fatigue stress.…”
Section: Fatigue Strain Evolution Modelmentioning
confidence: 99%
“…If we know the relationship of the curve and the cycles, we are able to qualitatively describe the evolution of the material fatigue strain, which will provide the basis for the behavior of the material evaluation. In numerous constant amplitude fatigue tests, it is shown that the total longitude deformation and the residual deformation of the concrete will display the universal and stable three-stage law [1][2][3][4][5][6], which presents firstly the rapid growth stage, then the stable growth stage, and ultimately the rapid growth stage. This is suitable for not only the ordinary concrete, lightweight aggregate concrete, high strength concrete, or fiber reinforced concrete, but also the compression fatigue, tension fatigue, bending fatigue, uniaxial fatigue, or multiracial fatigue.…”
Section: Introductionmentioning
confidence: 99%